Course Recommendation of College Education Platform Based On Collaborative Filtering Algorithm - GE CHANGSHENG; CAO YANJIE; DOU XIAOXIAO (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Based on the educational informatization paradigm of modern education theory, big data analysis and artificial intelligence of the new engineering system, colleges and universities have formed a student-centered, ability oriented, continuous iteration of qualification evaluation and curriculum quality. This research is based on collaborative filtering algorithm. The main purpose of the project is to provide a platform for students and parents to find the college education that best suits their needs. This will be achieved by considering all factors, such as price, location, facilities, courses provided and other functions, in order to establish a good recommendation system. We have developed most products, but we still need some funds to complete successfully. Our goal is $50000, which will help us create an MVP (minimum viable product) version of the application so that we can get feedback.